2015
DOI: 10.1073/pnas.1415473112
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt tectonics and rapid slab detachment with grain damage

Abstract: A simple model for necking and detachment of subducting slabs is developed to include the coupling between grain-sensitive rheology and grain-size evolution with damage. Necking is triggered by thickened buoyant crust entrained into a subduction zone, in which case grain damage accelerates necking and allows for relatively rapid slab detachment, i.e., within 1 My, depending on the size of the crustal plug. Thick continental crustal plugs can cause rapid necking while smaller plugs characteristic of ocean plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…The simple ODE in Eq. (40) was elaborated into a system of ODE's to study the impact of coupling between grain-sensitive rheology and grain-size evolution with damage on slab detachment (Bercovici et al, 2015). The more elaborated system of ODE's had to be solved numerically.…”
Section: Lithospheric Neckingmentioning
confidence: 99%
See 2 more Smart Citations
“…The simple ODE in Eq. (40) was elaborated into a system of ODE's to study the impact of coupling between grain-sensitive rheology and grain-size evolution with damage on slab detachment (Bercovici et al, 2015). The more elaborated system of ODE's had to be solved numerically.…”
Section: Lithospheric Neckingmentioning
confidence: 99%
“…The more elaborated system of ODE's had to be solved numerically. Bercovici et al (2015) showed that weakening due to grain size reduction and damage in polycrystalline rock can significantly accelerate necking and hence slab detachment, so that detachment can occur in about 1 My.…”
Section: Lithospheric Neckingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its simplicity, relative to the full set of equations and , the pinned state limit is frequently used in geodynamic applications of grain damage theory (Bellas et al, ; Bercovici et al, , ; Mulyukova & Bercovici, , ).…”
Section: Grain Damage Physicsmentioning
confidence: 99%
“…Here we explore an alternative view that material strength might not be instantaneously restored to its full pre-yielded value and acknowledge that the geological material may have been weakened as a result. We use a computationally efficient way of parameterizing the effective viscosity that may result due to any number of mechanisms that may be active subsequent to leaving the high stress bending region, including the development of weakened tectonic fabrics or subgrid faults in the lithosphere, in addition to the possible activation of Peierls creep, damage rheology, or other non-Newtonian rheologies (Kameyama et al, 1999;Bercovici, 2003;Garel et al, 2014;Bercovici et al, 2015;Holt et al, 2015a).…”
Section: Rheologymentioning
confidence: 99%